Palm sugar business development model through mold-making - Purbaningsih, Yuli; Helviani; Sinaini, La; Nursalam; Kasmin, Muh Obi (Asian Journal of Agriculture and Rural Development, 2025)
This research aims to develop a palm sugar business model through the engineering of palm sugar molds. The study was conducted using qualitative research methods, based on social phenomena and issues occurring in the development of the palm sugar business. The result of this research is a design for a modern palm sugar molding unit based on a stainless-steel machine, which will serve as a role model for palm sugar business actors to ensure that the production process is carried out more safely and hygienically (efficiently), as well as more quickly (effectively). The practical implication of this research is that the development of a stainless steel-based palm sugar molding unit can significantly enhance cleanliness and safety standards in the palm sugar production process. By adopting this modern design, palm sugar business operators can produce sugar more efficiently and effectively, reducing production time and improving the quality of the final product. Additionally, with a more standardized and hygienic process, businesses can meet higher health standards, open new market opportunities, and increase consumer trust. The implementation of this molding machine can also encourage overall improvements in production practices and enable larger-scale production without compromising quality.